A Large‐Area, Flexible, and Flame‐Retardant Graphene Paper. (27th January 2016) - Dong, Liye; Hu, Chuangang; Song, Long; Huang, Xianke; Chen, Nan; Qu, Liangti
Abstract : Similar to the paper‐making process, the efficient flame retardant graphene paper is conveniently obtained by using graphene oxide (GO) and hexachlorocyclotriphosphazene (HCCP) aqueous pulp. The "paper pulp" can also conceivably be used as ink to make other hydrophilic films become flame retardant paper. Further, the as‐prepared reduced GO‐HCCP paper (RGO‐HCCP paper), compared with GO‐HCCP paper, can maintain its intact structure for a longer time in an ethanol flame. As a consequence of these preparation methods, the bearing temperature of the as‐prepared graphene papers shows a significant increase. Abstract : A flame‐retardant piece of free standing graphene paper is developed by using graphene oxide and hexachlorocyclotriphosphazene. The graphene paper shows efficient flame retardant properties in combustion. The improved thermal stability of graphene opens new possibilities for various applications, including the use as civil, military, and aerospace flame retardant.